Ecological relationships between phytoplankton communities and different spatial scales in European reservoirs: implications at catchment level monitoring programmes - Cabecinha, Edna (2009)
Phytoplankton communities are structured by factors acting over temporal and spatial scales. Identifying which factors are driving spatial patterns in aquatic communities is the central aim of ecology. In this study, data sets of phytoplankton communities and nvironmental data of two Portuguese servoirs types (lowland ‘‘riverine reservoirs’’ and higher altitude ‘‘artificial lake reservoirs’’) were used to determine the importance of environmental variables at different spatial (geographical, regional and local) and time scales (seasons, years) on the community tructure. In all the data sets, the multivariate ordination technique